A multi-scenario analysis to improve layout efficiency - Lobato, Simão Duarte (2019)
The ability to compete is paramount and efficiency, regardless of the organisations’ overall approach, is an issue companies continuously strive for. In every supply chain, the logistics costs represent a large portion of overall costs, and hence the warehousing costs. Although the storage of products by itself does not add value to the customer, it has an immediate impact on these operation costs. Lauak Portugal is a partner factory of Groupe Lauak, a French group that owns a set of industrial companies supplying the aeronautical market. Aiming the layout costs reduction, it is inside its final products warehouse that this research is carried out. Excluding inventory costs, the picking activity alone represents about 55% of the warehousing costs (Drury, 1998). Additionally, travelling during the picking activity is estimated to require about 50% of the time of the resources (Tompkins et al., 2010). Supported by this assumptions, 44 scenarios are analysed and compared, mixing storage assignment policies and alternative picking routes strategies. Both qualitative and quantitative approaches are used in this research, based on data collected from interviews, observation, documentation and archival records. A case study approach is conducted following literature recommendations (Voss et al., 2002; Yin, 2018). Findings showed that travelling distance can be reduced by about 64% when the class-based storage is used, following their picking frequency, along with a pre-selected picking route.